Diagnostic and Therapeutic Alternative Medicine in Healthcare Practice: A Comprehensive Review - Wibawa, Adhi Dharma; Risaldi, Randi Achtiar; Kartowirejo, Faiz Arrafi; Suryani, Siti Dwi; Kendenan, Valentino; Ahmad, Naufal; Sianipar, Cintya Melati; Zuhrotul Laili, Nazwa (Journal of Medicine and Health Technology, 2025)
Treatment that combines local wisdom and modern knowledge is increasingly developing. This treatment is known as alternative medicine, which differs from conventional medicine because it is intended for therapy or diagnosis and has a close relationship with cultural practices such as community spirituality. This review aims to comprehensively understand alternative medicine, including its background, reasons for its use and debates about its effectiveness and safety. In addition, this review aims to improve readers' understanding of alternative medicine so that they can make better decisions in choosing the right treatment. This review compares two types of alternative medicine, diagnostic and therapeutic medicine. Diagnostic alternative medicine focuses on identifying imbalances in the body that are believed to cause disease. In contrast, therapeutic alternative medicine is based on traditional beliefs, is empirical, or has been used for centuries. The debate about the credibility of these two alternative medicine methods is ongoing, and strong scientific evidence is needed to support their effectiveness and safety. In addition, it is important to discuss the regulation and standardization of practice for practitioners of these alternative medicines. This review emphasizes the importance of consulting a specialist before starting any alternative treatment to ensure its safety and suitability for the patient's health condition. This review helps to increase readers' understanding of alternative medicine, so they can make better decisions in choosing the right treatment.